Promoting quality and productivity in the National Automobile Industry Co. Ltd - Rahmat, Kisai Bin (1991)
The National Automobile Industry Co. Ltd. (Proton) of Malaysia manufactures passenger cars for the Malaysian and foreign markets. In promoting quality and productivity, Proton has adopted specific policies and approaches in all its management and manufacturing activites. Quality is emphasized in the design, materials and manufacturing process while productivity is emphasized at all levels at work covering efforts to reduce manhours, material wastage and utilities through regular improvement activities. The current basic strategies employed by Proton to achieved its objectives are rigorous and meticulous training of personnel, establishment of Quality Control Circles (QCC) and the standardization of procedures. future strategies would be through automation and the use of high technology.
Keywords: Public administration -- Malaysia; Government productivity; Industrial productivity -- Laws; The National Automobile Industry Co. Ltd. (Proton) Malaysia